2004
DOI: 10.1080/01443610410001660913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-abortion counselling in a semi-urban town of Western Nigeria

Abstract: This study is designed to evaluate the impact of post-abortion counselling in bringing about changes in sexual behaviour among patients who had treatment for an induced abortion and/or its complication in the department of gynaecology and obstetrics of Wesley Guild Hospital Ilesa and Folasola Specialist Hospital between January 1999 and December 2001. A structured questionnaire designed to evaluate the impact of counselling was administered to 108 patients, who formed part of 238 patients who had undergone ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…However, after treatment, the practice of routinely counseling women on family planning increased this proportion to 84.5% – a near doubling of contraceptive uptake. Although several studies have reported increase in uptake of family planning after postabortion counseling in Nigeria [23–25], none has documented an increase of this magnitude. The authors believe this to be due to the intense nature of the intervention and because trained midwives were involved in the counseling of the women.…”
Section: Discussionmentioning
confidence: 93%
“…However, after treatment, the practice of routinely counseling women on family planning increased this proportion to 84.5% – a near doubling of contraceptive uptake. Although several studies have reported increase in uptake of family planning after postabortion counseling in Nigeria [23–25], none has documented an increase of this magnitude. The authors believe this to be due to the intense nature of the intervention and because trained midwives were involved in the counseling of the women.…”
Section: Discussionmentioning
confidence: 93%
“…The immediate post-abortion period offers a great opportunity to offer contraceptives to women. Several studies have attested to this fact [11][12][13]. The current study looked at the contraceptive preferences of clients who underwent an abortion episode at Komfo Anokye Teaching Hospital, Kumasi, and a tertiary referral centre.…”
Section: Introductionmentioning
confidence: 96%
“…Because many women resume sexual activity shortly after an uncomplicated abortion and fertility may return as early as 10 days after a first-trimester abortion [10], it is crucial that women who are not seeking another pregnancy are offered eff ective methods of contraception that they can use immediately after the abortion episode. Pre-and post-abortion counseling on use of contraception have been regarded as appropriate vehicles to decrease unwanted pregnancies and subsequent induced abortions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies both South African (see, for example, Fawcus et al 1997;Ward 1997;Janse van Vuuren 2001;Mhlanga 2003) and international (see Landy 1986;Steinberg 1989;Brien and Fairbairn 1996;Fasubaa and Ojo 2004;Elder and Laurence 2005) routinely conclude that counselling is an important component of termination of pregnancy service provision. The orthodoxy is that South Africa needs more and improved pre-and post-abortion counselling and that limited resources for counselling constitutes one of the major challenges to successful implementation of the CTOP Act (see Orner et al 2010, 50).…”
Section: Introductionmentioning
confidence: 99%